PENINGKATAN KEMAMPUAN MANAJEMEN KELAS DALAM KEGIATAN PBM MELALUI SUPERVISI KLINIS PADA GURU SD KEPUH UPT PPK JETIS - Siti Haryani (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2020)
The Purpose of this research is to: 1) to know the implementation of clinical supervision as an effort to improve the ability of teachers in PBM activities of Kepuh elementary school teachers. 2) Take a clinical supervision measures to improve the ability in class management of Elementary School teacher. This research includes the type of school action research. The data collection techniques undertaken are with observations, tests and documentation as well as research instruments. Data analysis is done in every single round of action, this study implemented 2 cycles of research. Each cycle consists of four stages planning, implementation the plan, observing the implementing of the plan and reflecting or evaluation. The Setting of this research is the classroom teachers of SD kepuh of UPT PPK Jetis. The results showed that the teacher’s ability are improved.